Strategi Guru IPS dalam Menggunakan Metode Pembelajaran Jigsaw untuk Membentuk Karakter Peserta Didik yang Bertanggung Jawab - Raudhatul Jannah; Amini Amini; Rafida Adilla; Risky Hardiansyah; Abdul Rahman Siregar (Journal on Education, 2023)
In each learning process there are various kinds of teacher strategies to carry out the learning of students. One of them used by the teacher when learning is to use the method in learning. The learning strategy is one of the factors that will determine the success of learning. With the existence of a learning strategy, teachers also hope that learning can achieve more optimal results in accordance with what is aspired to. Using the learning method is one of the strategies used by the teacher so that the teacher can also see how far the students are active in learning and how these students can carry out their responsibilities as educators in carrying out the learning process. So, that way the teacher can also see the character of the student and the most important thing is the formation of the student's character by evaluating himself during the learning process.